BEHAVIOR OF NATURAL AND TREATED SOIL WITH MICROORGANISMS UPON VARIOUS WATER CONTENT DUE TO DYNAMIC LOAD - Albert Allowenda PS; Ria A. A. Soemitro; Trihanyndio Rendy Satrya (Institut Teknologi Sepuluh Nopember (ITS), 2022)
The use of microorganisms such as fungus or bacteria as stabilizers in soil stabilization was not so often being practised or experimented with in the field. Also, there was so little information about this type of stabilization being carried out even in a minor scale experiment such as a laboratory experiment. A previous study using a fungus with the type of Rhizopus oligosporus resulted in a significant increase in soil consistency under certain water content conditions in the soil with a high percentage of the sand component. Therefore, this experiment is intended for analyzing loose sandy soil in Kulonprogo where the New Yogyakarta International Airport was built and the soil itself was highly saturated and vulnerable to experiencing liquefaction phenomenon. Liquefaction is a condition in highly saturated loose sandy soil where highly excess pore water pressure causes the loss of effective stress between soil particles simultaneously due to dynamic load and it will have an impact on building damage or failure laid on that type of soil. Therefore, an experimental model was carried out to analyze the behaviour of loose sandy soil when stabilized with Aspergillus fungus as the microorganisms. The soil stabilized by Aspergillus will be tested for liquefaction due to dynamic load and it will analyze the changes in soil parameters after the soil stabilization. The experiment shows that the appropriate percentage of soil mixture consists of ordinary sand with a percentage of 62% plus silt and clay with a percentage of 38%. Aspergillus fungus isolates at a concentration of 10-2 showed good tissue growth without the presence of foreign substances. Based on the results of the shear strength test in the form of Triaxial UU (Unconsolidated Undrained) experiment on remoulded soil that was given a stabilizer in the form of Aspergillus, it increased the cohesion parameter (c) when the remoulded soil was given Aspergillus with a percentage of 6% at a water content of 48,5%. From the soil parameters, liquefaction analysis is performed and resulted that there was still a high probability of liquefaction occurring because, from the analysis, the safety factor (SF) was lower than the minimum safety factor (SF) required.